2014
DOI: 10.1103/physreve.89.062140
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic description of the Ising antiferromagnet on a triangular lattice with selective dilution by a modified pair-approximation method

Abstract: The pair-approximation method is modified in order to describe systems with geometrical frustration. The Ising antiferromagnet on a triangular lattice with selective dilution (Kaya-Berker model) is considered and a self-consistent thermodynamic description of this model is obtained. For this purpose, the Gibbs free energy as a function of temperature, concentration of magnetic atoms on the selected sublattice, and external magnetic field is derived. In particular, the phase diagram is constructed and a compari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
2
7
0
1
Order By: Relevance
“…60 A highly inhomogeneous fluorine coverage was found to produce multilayer islands, folds, wrinkles, and ripples, all containing a lower content of fluorine, consequently forming a conductive superstructure through which the charge transport, mediated by itinerant π-electrons, occurred preferentially. 60 61,62 (see Methods Section below for details) indicated that the ferromagnetically ordered state was stable up to temperatures exceeding 300 K, in good agreement with the experimentally derived TC. The electronic structure displayed as density of states (DOS) of the C18(OH)4F6 model provided insights into the magnetic exchange mechanism in the G(OH)F system (see Figure 4b).…”
Section: Resultssupporting
confidence: 77%
“…60 A highly inhomogeneous fluorine coverage was found to produce multilayer islands, folds, wrinkles, and ripples, all containing a lower content of fluorine, consequently forming a conductive superstructure through which the charge transport, mediated by itinerant π-electrons, occurred preferentially. 60 61,62 (see Methods Section below for details) indicated that the ferromagnetically ordered state was stable up to temperatures exceeding 300 K, in good agreement with the experimentally derived TC. The electronic structure displayed as density of states (DOS) of the C18(OH)4F6 model provided insights into the magnetic exchange mechanism in the G(OH)F system (see Figure 4b).…”
Section: Resultssupporting
confidence: 77%
“…It should be noted from Ref. [30] that the specific heat displays no singular part but shows pronounced peaks corresponding to the Néel temperatures. This property is expressed as α = 0 for the AFIM in pair approximation and the scaling behaviour of R is, therefore, ∼ α−2 which is the same as α > 0.…”
Section: Thermodynamic Curvature Scalar For the Antiferromagnetic Isimentioning
confidence: 99%
“…Considering the magnetic Gibbs energy surface in the statistical Bethe (or pair) approximation and using the equilibrium conditions, they obtained two equations (also known as the Bethe equations) for the order parameters. In advanced years, the Bethe approximation (a useful tool for studying spin systems [25][26][27]) was also performed to calculate phase diagrams of AFIM in various lattice geometries [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…However, their study involves only small system with sizes up to 30×30 and features no finite-size scaling analysis. Other studies analyzed the Kaya-Berker model using Monte Carlo (MC) simulations [21,22], effective-field theory (EFT) [23] and a modified pair-approximation (PA) method [24]. The EFT approach is based on a cluster approximation with clusters comprised of only a single spin and interactions with their nearest neighbors [25], which is quite similar to HSMF.…”
Section: Modelmentioning
confidence: 99%